Analisis Kepuasan Pengguna Canva Pada Mahasiswa Fakultas Ekonomi Universitas Garut Dengan Menggunakan Metode TAM - Huznul Nurullia; Rifqi Taufik Rachman; Seli Sagita Ramadhan; Ramayani Yusuf (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This study aims to determine how satisfied students of the Faculty of Economics, Garut University are with the Canva application. External factors, such as ease of use, benefits, and desire to continue using it, are the focus of this study. This study uses quantitative methods, the population in this study are active students of the Faculty of Economics, Garut University, totaling 2033 and using probability sampling techniques and a sample of 100 respondents was taken using the slovin formula. To determine the level of user satisfaction with the application, the Technology Acceptance Model (TAM) was used. The results stated that Canva supports the use of the system and has a feeling of usefulness, convenience, and usability that is considered important. In addition, the results show that users' desire to use the system affects their level of happiness by 80%.